Can Russia reorient its trade and financial flows? - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
Russia's invasion of Ukraine and resulting sanctions have substantially hurt Russia's economic relations with developed economies. Countries imposing sanctions on Russia accounted for half of Russia's foreign trade and over half of foreign financial flows before the war. We analyse the development of Russia's trade and financial relations in recent months and find that Russia's success in reorienting its trade and investment flows has been mixed.
urn:nbn:fi-fe2022120569390
Keywords: 330; Russia; Ukraine; sanctions; trade; FDI